The disparities of environmental health awareness among rural-urban community in Klang Valley, Malaysia - Mohd Zainuddin, Nural Farah Ain; Vivien, How (Kalpana Corporation, 2016)
Environmental health awareness programmes are frequently focused among the urban residents than the rural residents, making these community experience disparities across a significant number of health status measures and health outcomes. To determine the environmental health awareness level and examine the contributing factors of the disparities among rural and urban community. This cross-sectional pilot study recruited 60 rural and 60 urban residents through simple random sampling around Klang Valley. A validated questionnaire which consists of 2 sections : Section A (socio-demographic background) and section B (Comprehensive Environmental Health Checklist) were used as the assessment tool. Urban community has significance higher awareness score as compared to rural community (p<0.05). While examining the potential contributing factors that causes disparities of awareness levels, 41.1% of the variation in the environmental awareness among urban residents are due to their education level, duration of stays in Klang Valley and household income, whereas; age, educational level and household income contribute to atleast 53.6% of the variation of environmental health awareness among rural residents. The provision of accurate and timely information about environmental health to both rural and urban residents will translate into beneficial practices of self-coping capacity and become resourceful in tackling environmental health hazards in their living environments.